Выбор оптимальных параметров криптосистемы SPHINCS+ - Марухненко, А.; Халимов, Г. З.; Янко, А. (ХНУРЕ, 2019)
The article describes a structure and parameters of the SPHINCS+ cryptosystem. The right choice of parameters allows you to optimize system performance relative to the time and memory costs. We propose few sets of parameters for 384 and 512-bit security.
Keywords: ЭЦП на основе хеш-функций; SPHINCS; постквантовая криптография; дерево Меркли